Conjugates of 8-[2,2’-bipyridinyl]coumarins as potential chemosensors for Al3+, Cu2+, Cd2+, Zn2+ ions: synthesis and photophysical properties - Ainur D. Sharapov; Ramil F. Fatykhov; Igor A. Khalymbadzha; Dmitry S. Kopchuk; Igor L. Nikonov; Anastasiya P. Potapova; Yaroslav K. Shtaitz; Pavel A. Slepukhin (Chimica Techno Acta)
In this work, we report the synthesis of novel coumarin-bipyridine conjugates using a sequence of C–C coupling reaction between 5,7-dimethoxycoumarins and 3-pyridyl-6-aryl-1,2,4-triazines followed by the Boger reaction with norbornandiene to obtain 8-[2,2'-bipyridyl]-5,7-dimethoxycoumarins. Photophysical properties were investigated for the obtained series of 8-[2,2'-bipyridyl]-5,7-dimethoxycoumarins: absorption and emission wavelength maxima are in the region of 212–296 and 401–410 nm, respectively; Stokes shifts are up to 116 nm, and fluorescence quantum yields are up to 15.0%. It was found that titrating the conjugates with Al3+, Zn2+, and Cd2+ ions results in an increase in the intensity of the emission maxima of the complexes, while the opposite effect was observed in the case of titration with Cu2+ ions. These findings suggest that the studied compounds may be considered as promising chemosensing materials. Finally, a positive solvatochromism of 8-[2,2'-bipyridyl]coumarins and their metal complexes was established. The experimental data are supported by mathematical calculations according to the Lippert-Mataga equation and Kosower diagram.